SISTEM PENDIDIKAN ISLAM MENURUT H.O.S COKROAMINOTO (Konsep Muslim Nasional Onderwijs, Historis dan Globalisasi) - Wildan Rusli (Institut Agama Islam Negeri Purwokerto, 2016)
H.O.S. Cokroaminoto is one of the imprtant figures in Indonesian education. He was famous with his concern in education, especially with his briliant concept of Moeslim National Ondewijs, an educational concept adressed to natives of Indonesia. In his concept of Moeslim National Ondewijs, H.O.S. Cokroaminoto explained the principles of democracy and society on the basis of Islam. The principles were then applied in the teaching of Aqidah Akhlaq, Qur’an and Hadits, Fiqih, The History of Islamic Culture, etc. those are the ideal materials that should be taught at schools. Besides concerning with cognitive aspects, education should care about: 1) growing sense of independence and democracy; 2) bravery, sincerity, and truth; 3) spirituality, good attitude and behavior; 4) religiosity and simplicity. The concepts are relevant to be applied in Islamic education of the present time.